2013
DOI: 10.1007/s00595-013-0666-6
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic evaluation of a mechanical anastomotic stapler used by Japanese surgeons

Abstract: Purpose The satisfaction rating of currently available mechanical staplers for Japanese surgeons with small hands is low. To identify the issue, we examined the relationship of hand dimensions and grip force with the operation force of a mechanical circular stapler. Methods Hand dimensions and grip force were measured in 113 Japanese surgeons (52 men and 61 women). We then evaluated the relationship between grip width and the operation force required to push the lever of the stapler, at three points on the lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…Similarly, to quantify the change in percept area, the mean area of the percept for each week was compared to the mean area for the previous week. The distances were converted to millimeters using the average hand length of 189 mm (as measured from the tip of the middle finger to the wrist) and average palmar area of 75 cm 2 of a human male ( Agarwal and Sahu, 2010 ; Ilayperuma et al, 2009 ; Kono et al, 2014 ; Martin and Nguyen, 2004 ; Rhodes et al, 2013 ; Zafar et al, 2017 ). All electrodes that were tested in at least two of the weeks were included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, to quantify the change in percept area, the mean area of the percept for each week was compared to the mean area for the previous week. The distances were converted to millimeters using the average hand length of 189 mm (as measured from the tip of the middle finger to the wrist) and average palmar area of 75 cm 2 of a human male ( Agarwal and Sahu, 2010 ; Ilayperuma et al, 2009 ; Kono et al, 2014 ; Martin and Nguyen, 2004 ; Rhodes et al, 2013 ; Zafar et al, 2017 ). All electrodes that were tested in at least two of the weeks were included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…It is logical from a tissue mechanics perspective that undue/erratic movement at the anastomotic site could result in microvascular trauma and fractures at the bowel interface, potentially compromising the anastomosis. Moreover, several previous studies have demonstrated that some surgeons are simply incapable of generating the grip-strength force required to fire circular staplers [2, 3]. Design improvements in circular stapling technology that enhance the device-to-user interface (i.e., improve handling, reduce force-to-fire requirements) whilst simultaneously addressing issues with device-to-tissue interaction (i.e., reducing unwanted movement at the anastomosis during construction) have the potential to decrease the rate of technical errors and lead to improvements in clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that some surgeons are simply unable to generate the grip strength force to fire circular staplers [2,3], and this may be an important factor in the aforementioned high rate of technical errors in their use to form anastomoses. The addition of power to the circular stapler has overcome the force to fire barrier in stapling.…”
Section: Discussionmentioning
confidence: 99%
“…Since that time there has been little improvement in the circular stapler function, although changes have been made to the staples and their configuration. Surgeons continue to experience difficulty in firing the devices [2,3], and this can lead to an unacceptably high rate of technical errors with manual circular staplers [4].…”
Section: Introductionmentioning
confidence: 99%